The Ai Khanoum Papyrus, Xenocrates’ and Aristotle’s Fragment: Some Textual and Exegetical Suggestions - Pasanisi, Davide (Revista Archai, 2025)
In this article, I intend to reconstruct the current state of research concerning the Ai Khanoum papyrus, found in Afghanistan in 1977, which contains a fragment of a dialogue on a Platonic subject dating from the second half of the 3rd century BCE. By reviewing existing studies, I present new arguments in support of certain exegetical proposals. In particular, I adopt the theory that the doctrine discussed in this brief text can be traced back to Xenocrates. Additionally, I support the position of those scholars who attribute the fragment to the lost Aristotelian work De philosophia, likely brought to Ai Khanoum by the Peripatetic Clearchus of Soli. This analysis also incorporates a newly proposed reconstruction of the Greek text, which is more closely aligned with the ink traces visible in photographs of the now-lost original, as well as a subsequent new Italian translation that accounts for the peculiarities and roughness of the Greek text.